The Analysis of the Students’ English Achievement (A Case Study on the Students of Islamic Early Childhood Education of Islamic College of Auliaurrasyidin) - Kurniawan, Nova Adi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2023)
Today, mastery of more than one language becomes a phenomenon that attracts the attention of people, especially young people as the nation’s successor. However, the results of learning English for most students, including university students, are still very poor. This article aims to analyze students’ learning achievement, and provide an overview of the problems they faced in learning English. This study is qualitative research. This is focused on the English learning achievement of 1st semester students of the Islamic Early Childhood Education (PIAUD) Study Program of STAI Auliaurrasyidin. Data were collected using in-depth interview and documentation. They were analyzed using the Miles and Huberman model which consists of data reduction, data display, and conclusions. The results showed that the students’ low English learning achievement were caused by the English sentence and grammatical structure that often confusing, poor of vocabulary knowledge that impacts on the difficulty in translating English sentences. In addition, lack of self-confidence also triggered students’ low learning achievements.